EVALUASI PERAN INCOME AUDIT SEBAGAI BAGIAN DARI SISTEM PENGENDALIAN INTERNAL DI HOTEL NOVOTEL LOMBOK - Lalu Ariel Azmar Vivaldi; Iman Waskito; Wulandari Agustiningsih (Politeknik Negeri Ambon, 2026)
Introduction: This research aims to evaluate the role of income audit within the internal control system at Hotel X Lombok, emphasizing the importance of accurate and reliable revenue reporting.Methods: This study adopts a qualitative case study approach. Data were collected through semi-structured interviews, direct observation, and documentation involving key informants from the finance and operational departments, including the income auditor, financial controller, general manager, front office manager, food and beverage manager, and general cashier. The data were analyzed using deductive thematic analysis based on the five components of the COSO Internal Control Framework.Results: The results show that the income audit function plays a crucial role in maintaining the accuracy and timeliness of daily revenue reporting. The application of clearly defined standard operating procedures, layered verification mechanisms, and integrated information systems significantly strengthens revenue control. Although operational errors still occur, particularly those arising from human error, most issues are identified and resolved promptly through effective coordination among departments.Conclusion and suggestion: Overall, the implementation of the income audit at Hotel Novotel Lombok has enhanced the effectiveness of the internal control system and supported financial transparency and accountability. This study provides empirical insights into the practical application of the COSO framework in the hospitality sector it suggests that management should continuously improve system integration and interdepartmental coordination to reduce revenue-related risks further. Keywords: COSO framework, Fraud risk, Hospitality industry, Income audit, Internal control system